2006
DOI: 10.1094/pd-90-0840
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prediction of Soybean Rust Entry into the Continental United States

Abstract: This special report demonstrates the feasibility of long-term prediction of intercontinental dispersal of Phakopsora pachyrhizi spores, the causal agent of the devastating Asian soybean rust (SBR) that invaded the continental United States in 2004. The climate-dispersion integrated model system used for the prediction is the combination of the particle transport and dispersion model (HYSPLIT_4) with the regional climate prediction model (MM5). The integrated model system predicts the trajectory and concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 15 publications
1
46
0
4
Order By: Relevance
“…Pham et al (2009) confirmed that the rust isolates resulting in a susceptible reaction in PI 200492 already existed in Brazil by 2001. These findings suggest that initial entry of the pathogen was achieved by its long distance movement from Central or South America (Isard et al 2005, Pan et al 2006. In addition, the pathogen genotype that could defeat Rpp1 in PI 200492 was restricted by the subsequent winter season, lost, and then never reestablished in the US, despite urediniospores of such populations that could be reintroduced from Central or South America.…”
Section: Discussionmentioning
confidence: 94%
“…Pham et al (2009) confirmed that the rust isolates resulting in a susceptible reaction in PI 200492 already existed in Brazil by 2001. These findings suggest that initial entry of the pathogen was achieved by its long distance movement from Central or South America (Isard et al 2005, Pan et al 2006. In addition, the pathogen genotype that could defeat Rpp1 in PI 200492 was restricted by the subsequent winter season, lost, and then never reestablished in the US, despite urediniospores of such populations that could be reintroduced from Central or South America.…”
Section: Discussionmentioning
confidence: 94%
“…Given that spores of are capable of long-distance travel via air currents, aerobiological models have been proposed for risk assessment and seasonal ASR prediction (Isard , 2005, Pan , 2006). a climate-dispersion integrated model system developed for simulating long-distance and long-term transportation of using climate forecast over one month in advance (Pan , 2006). The application is based on the atmospheric transport model NOAA ARL HYSPLIT_4 (HYSPLIT -) (NOAA, 2006).…”
Section: Aerobiological Modelsmentioning
confidence: 99%
“…The climate-dispersion integrated model, constructed by researchers from Iowa State and St. Louis Universities (Pan et al 2006), integrates the particle transport and dispersion components of the NOAA Air Resource Lab HYSPLIT_4 model (Draxler and Hess 1998) with the Pennsylvania State University/National Center for Atmospheric Research mesoscale MM5 regional climate prediction model (Dudhia and Bresch 2002). The resulting forecasting system was used to predict the trajectory and concentration of spores of P. pachyrhizi based on three-dimensional wind advection and turbulent transport.…”
Section: Pipe Sentinel Plot Monitoring and Forecastingmentioning
confidence: 99%
“…The model incorporates a simple viability criterion for aerial spores as well as both wet and dry deposition, and it was configured with a domain that included the southeastern United States with a resolution of 40 km. The modeling system was used to predict spore movement in the southeastern United States a month in advance during the 2005 to 2007 growing seasons (Pan et al 2006;Yang et al 2007). …”
Section: Pipe Sentinel Plot Monitoring and Forecastingmentioning
confidence: 99%